Identification of Bumdes (Village Owned Enterrise) Problems in Villages of Gunung Sari District of Look Barat Regeny - Inapty, Biana Adha; Fikri, M Ali; Waskito, Iman (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2022)
BUMDes (Village Owned Business) is a business unit that is hoped to become a revenue generating unit for the Village Government In reality, Bumdes faces many problems. Related to this fact, our research tries to identify problems that occur in the field. Methodology of this research is qualitative research with village heads, BUMDes managers, and local village assistants as informants. The results show that the problems that are still faced by BUMDes are low quality of human resources, regulation, the small percentage of capital participation by villages to BUMDES, bookkeeping, evaluation, cooperation has not been widely carried out with outside parties, products from the community have not been accommodated by BUMDes, much of village potential have not been explored and developed. We suggest the importance of a strong commitment of the leaders, improve the human resources capability, create collaboration with many parties, explore the village potentials. The implication of this research is hoped to become an additional information for the Village Government and Bumdes in managing their business units